1995
DOI: 10.1021/bi00016a041
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Selection of RNA Ligands to Substance P

Abstract: RNA ligands to the tachykinin substance P have been selected from a large pool of random sequence RNA molecules. Substance P is an undecapeptide that plays a variety of roles as a neurotransmitter and neuromodulator in the central and peripheral nervous system of mammals. A systematic evolution of ligands by exponential enrichment (SELEX) procedure was used to isolate RNAs that bind substance P immobilized on a solid support. RNAs that also bind substance P in solution were identified, and the tightest binder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 31 publications
3
72
0
Order By: Relevance
“…These affinities match with those obtained for other nonconstrained, non-nucleic acid binding peptides for which aptamers have been selected (Nieuwlandt et al 1995;Weiss et al 1997;Blind et al 1999;Proske et al 2002b). To evolve these tight-binding aptamers we used affinity maturation of the originally selected binders.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These affinities match with those obtained for other nonconstrained, non-nucleic acid binding peptides for which aptamers have been selected (Nieuwlandt et al 1995;Weiss et al 1997;Blind et al 1999;Proske et al 2002b). To evolve these tight-binding aptamers we used affinity maturation of the originally selected binders.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, the membraneproximal epitope contains three arginine residues and fewer acidic amino acids, whereas the C-terminal half does not contain any basic amino acids but a cluster of acidic ones. Tight-binding aptamers have been observed before to preferentially evolve to epitopes that contain positively charged amino acid residues, presumably utilizing electrostatic interactions (Nieuwlandt et al 1995;Kimoto et al 1998;Blind et al 1999). In addition, our anti-B1-CT aptamers add to a series of other aptamers that target proteins implicated in neurodegenerative diseases, in particular aptamers directed against various forms of the prion protein (Weiss et al 1997;Proske et al 2002a;Rhie et al 2003;Sayer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that aptamers form stable and specific complexes with a range of different targets, including small molecules such as amino acids and highly complex proteins and whole viruses. [3][4][5][6][7][8][9][10] These specialized molecules are analogs to antibodies in specificity and affinity, but have the potential advantage of being reproduced by chemical synthesis and be more easily labeled with fluorescent or other reporters during their synthesis. Consequently, they are considered potential therapeutic agents and also thought to rival antibodies in immunoassay-like analyses.…”
mentioning
confidence: 99%
“…The term 'aptamer' means 'to fit' (aptus) in Latin (6), which indicates two important properties of aptamers: i) their ability to fold into complex tertiary structures and recognize their targets with high affinity (low nM to high pM equilibrium dissociation constants); and ii) their specificity, somewhat analogous to antigen-antibody interactions. Using this technique, a number of aptamers that specifically recognize targets, such as metal ions (11)(12)(13), organic dyes and amino acids (14)(15)(16)(17), antibiotics (18,19) and peptides (20,21), as well as proteins of various sizes and functions (6,22,23), whole cells (24)(25)(26)(27), whole organisms (28), viruses (29) and bacteria (30), have been obtained (31)(32)(33). The SELEX process is based on the ability of these small oligonucleotides to fold into unique 3D structures that interact with a target with high specificity and affinity through such interactions as van der Waals surface contacts, hydrogen bonding and base stacking.…”
Section: Aptamers and Selexmentioning
confidence: 99%